1983
DOI: 10.1152/jappl.1983.55.6.1688
|View full text |Cite
|
Sign up to set email alerts
|

Hypervolemia and plasma vasopressin response during water immersion in men

Abstract: To investigate changes in plasma volume (PV) and osmolality as stimuli for plasma vasopressin (PVP) suppression and diuresis, seven normal healthy men (22-48 yr) were immersed to the neck for 4 h in a sitting position in tap water (34.5 degrees C) after overnight food and fluid restriction. Mean +/- SE urine volume was 823 +/- 123 ml/4 h; fluid intake was 400 ml/4 h, and mean negative water balance was 944 ml/4 h. Urinary sodium excretion increased from 0.77 to 1.25 mosmol/min (P less than 0.05) and UNaV from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1
2

Year Published

1989
1989
2009
2009

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 0 publications
2
13
1
2
Order By: Relevance
“…Body temperature must be elevated if dehydration occurs with decreasing sweat rate (Sawka et al 2001), because sweating is accompanied by loss of body fluid; however, the sweat rate at body temperature was not significantly different between PRE and POST in our study. The reduction of total body water or PV could activate the renin-angiotensin-aldosterone system (Greenleaf et al 1983;Hubschle et al 2001). In our study, plasma volume decreased by approximately 10% from the 1st to the 5th day and remained decreased until the 20th day of HDBR.…”
Section: Discussionsupporting
confidence: 48%
“…Body temperature must be elevated if dehydration occurs with decreasing sweat rate (Sawka et al 2001), because sweating is accompanied by loss of body fluid; however, the sweat rate at body temperature was not significantly different between PRE and POST in our study. The reduction of total body water or PV could activate the renin-angiotensin-aldosterone system (Greenleaf et al 1983;Hubschle et al 2001). In our study, plasma volume decreased by approximately 10% from the 1st to the 5th day and remained decreased until the 20th day of HDBR.…”
Section: Discussionsupporting
confidence: 48%
“…Most thermoneutral immersion (McCally 1964;Khosla and DuBois 1979;Harrison et al 1986;Ertl et al 1991), and all cold-water immersion studies have employed this indirect technique. However, a discrepancy in the indirectly-measured PV and Evans blue dye results during thermoneutral immersion was observed by Greenleaf et al (1983). Subsequently, Johansen et al (1992Johansen et al ( , 1995 demonstrated this approximation to underestimate the ''true'' PV response during thermoneutral immersion, as determined using a direct tracerdilution technique.…”
Section: Introductionmentioning
confidence: 99%
“…Accompanying the increased urine production is an increased loss of sodium (Na) and potassium (K) ions (natriuresis and kaliuresis) (Epstein et al 1975;Epstein 1978). These physiologic responses occur when subjects aze immersed in either cold Doubt et al 1988;Young et al 1987) or thermoneutral water (Epstein 1978;Greenleaf et al 1980;Greenleaf et al 1981;Greenleaf et al 1983;McCalley 1964). Exposure to cold air alone significantly increases diuresis and plasma volume loss (Young et al 1987); however, cold water immersion produces a more powerful stimulus Trippodo et al 1983).…”
Section: Introductionmentioning
confidence: 99%